ผลการดำเนินการด้านการแสดงความรับผิดชอบต่อสังคมของศูนย์พัฒนาปิโตรเลียมภาคเหนือ อำเภอฝาง จังหวัดเชียงใหม่ - อารุณี ศรีอินทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purposes of the study of “Results of Corporate Social Responsibility Operation of Northern Petroleum Development Center, Fang District, Chiang Mai Province” were: 1. Toundertake a feasibility study to see if the implementation of the project and responsible social activities of Northern Petroleum Development Centerwill solve community problems. 2. To study the potential of building a positive image and to have the Northern Petroleum Development Center be accepted from the local people. 3. To study the suggestions about the project and responsible social activities of Northern Petroleum Development Center. This was a quantitative research which used the questionnaire as a tool to collect all the data needed from the people who live near Northern Petroleum Development Center, T. Maeka in Fang District, Chiang Mai Province. A total of 370 people were selected.